Indelible Marks of Violence in Amrita Pritam’s Novel Pinjar - Poudel, Bimal Prasad (BMC Research Journal, 2025)
This paper examines the impact of the 1947 India-Pakistan partition through the lens of Amrita Pritam’s novel Pinjar (1950), which poignantly captures the harrowing experiences of women caught in the crossfire of religious and political upheaval. The narrative follows Pooro and Lajo, two women whose lives are irrevocably changed by the brutal violence of partition, symbolizing the countless women who were abducted, raped, and subjected to forced conversions during this tumultuous period. Through these personal stories, Pinjar highlights the gendered nature of violence during partition, where women's bodies became battlegrounds for religious and cultural conflict between Hindus and Muslims. The paper delves into how the trauma of partition disproportionately affected women, whose suffering was often a consequence of communal hatred, societal norms, and the breakdown of familial ties. By drawing on trauma theory as articulated by Cathy Caruth and Jeffrey Alexander, as well as gendered readings of partition violence by scholars like Urvashi Butalia, Ritu Menon, and Kamla Bhasin, this study critically analyzes Pinjar to argue that Pooro's fate mirrors the fate of thousands of women whose lives were irreparably altered by the partition. Ultimately, the paper underscores the deeply gendered dimension of partition violence, illustrating how women's suffering became emblematic of the broader socio-political trauma of the era.